Salt spray and abrasion resistant water-based paint for off-road forklifts and its preparation method

By adding hydrophobic fillers with amino and fluorine-containing groups to the off-road forklift water-based paint, the problem of insufficient salt spray resistance of water-based paint in high salt spray environments is solved, and the salt spray resistance, wear resistance and toughness of the coating are improved.

CN119060590BActive Publication Date: 2025-03-28ZHEJIANG UNFORKELEVATOR
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411133419.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-03-28
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

The existing water-based paint is easily penetrated by salt spray in high salt spray environments, resulting in the metal parts of off-road forklifts being easily rusted and insufficient salt spray resistance.

Method used

A hydrophobic filler containing amino groups and fluorine-containing groups is used to form chemical connections through reaction of amino groups with acrylic emulsion to enhance the connection between the filler and the coating substrate; a hydrophobic layer is formed by fluorine-containing groups, improving the salt spray resistance of the coating, and introducing fluorine atoms through trifluoroacetic anhydride to enhance the cohesion and hardness of the coating.

Benefits of technology

It significantly improves the salt spray resistance and wear resistance of off-road forklift coatings, extends the service life of the coating, and improves the toughness and adhesion of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of engineering machinery coatings, and in particular to a salt-fog-resistant and wear-resistant water-based paint for off-road forklifts and a preparation method thereof. The water-based paint comprises the following raw materials in parts by mass: 90-110 parts of acrylic emulsion, 0.3-1 parts of wetting agent, 1-2 parts of dispersant, 0.1-1 parts of defoamer, 20-40 parts of hydrophobic filler, 0.3-1.2 parts of anti-flash rust agent, 1-3 parts of thickener, 1.5-5 parts of cosolvent, 2-5 parts of adhesion promoter, 5-15 parts of pigment, and 40-80 parts of deionized water; the shielding filler comprises a filler, a silicon dioxide layer coated on the surface of the filler, and amino and fluorine-containing groups grafted on the surface of the silicon dioxide layer. The water-based paint of the present application has good wear resistance and salt-fog resistance, and can adapt to long-term use in environments with high salt-fog content such as ports.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of engineering machinery coatings, and in particular to a salt-spray-resistant and wear-resistant water-based paint for off-road forklifts and a preparation method thereof. Background Art

[0002] Rough-terrain forklifts are heavy-duty transport tools used in harsh outdoor environments. They are widely used in complex terrains such as docks, construction sites, mines, forests, and farms. In dock operations, especially, rough-terrain forklifts undertake the crucial tasks of cargo loading, unloading, stacking, and transportation. These working environments are often accompanied by challenges such as high humidity, high salinity, and heavy loads, placing high demands on the forklift's wear resistance and corrosion resistance.

[0003] Currently, forklift coatings on the market primarily fall into two categories: solvent-based and water-based. Solvent-based coatings are renowned for their excellent adhesion and durability, but they also pose challenges such as high emissions of volatile organic compounds (VOCs) and severe environmental pollution. In contrast, water-based coatings are gaining popularity due to their environmentally friendly properties. Using water as the primary solvent, they significantly reduce VOC emissions.

[0004] However, water-based paint has certain drawbacks in high-salt fog environments, such as those found in dock operations. Because water-based paint is highly hydrophilic, it is more susceptible to salt fog penetration in high-salt, high-humidity environments, resulting in poor corrosion resistance. Summary of the Invention

[0005] In order to alleviate the problem that the salt spray resistance of water-based paint used for off-road forklifts is insufficient, which causes the metal parts of off-road forklifts to be easily corroded, the present application provides a salt spray and wear-resistant water-based paint for off-road forklifts and a preparation method thereof.

[0006] In a first aspect, the present application provides a salt spray and wear resistant water-based paint for off-road forklifts, which comprises the following raw materials in parts by weight:

[0007] 90-110 parts of acrylic emulsion, 0.3-1 parts of wetting agent, 1-2 parts of dispersant, 0.1-1 parts of defoaming agent, 20-40 parts of hydrophobic filler, 0.3-1.2 parts of anti-flash rust agent, 1-3 parts of thickener, 1.5-5 parts of cosolvent, 2-5 parts of adhesion promoter, 5-15 parts of pigment, 40-80 parts of deionized water;

[0008] The shielding filler comprises a filler, a silicon dioxide layer coated on the surface of the filler, and amino groups and fluorine-containing groups grafted on the surface of the silicon dioxide layer.

[0009] Preferably, the preparation method of the hydrophobic filler is:

[0010] The filler is uniformly dispersed in deionized water to prepare a dispersion, the temperature is raised to 80-90° C., and the pH of the dispersion is adjusted to 8.5-10 with an alkaline solution; an ethanol solution of orthosilicate is added to the dispersion as a precursor to carry out a sol-gel reaction to obtain a reaction product; the precipitate is filtered, washed with water until neutral, and dried to obtain a coated filler;

[0011] The coated filler is added to an ethanol solution, the pH value is adjusted to 4-5, an aminosilane coupling agent is added, and the mixture is stirred for reaction for 0.5-1 hour, filtered, washed with water, and dried to obtain a silanized filler;

[0012] Prepare trifluoroacetic anhydride solution and heat it to 60-90° C., add silanized filler and sodium hydroxide solution, adjust the pH value to 8-9, react at constant temperature for 2-4 hours, filter, wash with water, and dry to obtain a hydrophobic filler.

[0013] Preferably, the filler is selected from at least one of mica, kaolin, calcium carbonate, talc and silica powder.

[0014] Preferably, the solvent of the trifluoroacetic anhydride solution is dimethyl sulfoxide or dimethylformamide.

[0015] Preferably, the mass ratio of the filler to the silicon dioxide in the precursor is 100:8-15.

[0016] Preferably, the molar ratio of the aminosilane coupling agent to trifluoroacetic anhydride is 1:0.15-0.25.

[0017] The water-based paint of the present application is based on acrylic emulsion and contains fillers with amino groups and fluorine-containing groups on the surface. Among them, the amino group can react with the acrylic emulsion to form a chemical connection, ensuring the firm connection of the filler and the substrate and improving the wear resistance of the coating. The fluorine-containing group stretches outward to form a hydrophobic layer, which can give the coating good salt spray resistance. In addition, the fluorine atom has a very high electronegativity, which makes it possible to have a strong intermolecular force between the fluorine atoms. This stronger intermolecular interaction can improve the cohesion of the coating, thereby increasing the hardness and wear resistance of the coating.

[0018] It should be noted that in the preparation of the hydrophobic filler of this application, a silica layer is first deposited on the filler substrate surface via a sol-gel method to provide sufficient active sites for modification. Then, amino groups are introduced onto the filler surface through the reaction of an aminosilane coupling agent with the silanol groups on the silica surface. Subsequently, trifluoroacetic anhydride reacts with some of the amino groups to introduce trifluoromethyl groups, imparting hydrophobic properties to the filler.

[0019] Preferably, the dispersant is a fluorocarbon surfactant and sodium dodecylbenzenesulfonate in a mass ratio of 1:1 to 2.

[0020] Preferably, the raw materials of the water-based paint include 2 to 5 parts of hydroxyl-terminated polybutadiene.

[0021] The combination of these dispersants ensures the full dispersion of the fluorinated hydrophobic filler in the acrylic emulsion matrix. By improving compatibility and electrostatic forces, they reduce agglomeration and precipitation of the hydrophobic filler, thereby ensuring the overall performance of the coating. The hydroxy-terminated polybutadiene can compensate for the loss of coating toughness caused by the introduction of fluorinated groups, helping to ensure the coating's wear resistance.

[0022] Preferably, the wetting agent is an acetylene glycol surfactant, for example, SURFYNOL 485.

[0023] Preferably, the defoaming agent is an organosilicon defoaming agent, such as BYK-024 and BYK-066N.

[0024] Preferably, the anti-flash rust agent is PFR289.

[0025] Preferably, the thickener is hydroxyethyl cellulose.

[0026] Preferably, the cosolvent is selected from at least one of propylene glycol phenyl ether, propylene glycol methyl ether, propylene glycol butyl ether, dipropylene glycol methyl ether, and dipropylene glycol butyl ether.

[0027] Preferably, the pigment is selected from at least one of titanium dioxide, iron oxide red, iron oxide black, iron oxide yellow, carbon black, phthalocyanine blue, phthalocyanine green, 139 yellow, 154 yellow, 151 yellow, 254 red, 73 orange, and 36 orange.

[0028] In a second aspect, the present application provides a method for preparing a salt spray and wear resistant water-based paint for an off-road forklift, comprising:

[0029] According to the raw material ratio of any of the above-mentioned water-based paints, weigh the raw materials in the formula amount for later use;

[0030] Add 60-70 wt% deionized water to the preparation container, add a wetting agent, a dispersant, and 40-50 wt% defoamer while stirring, stir evenly, then add pigment, hydrophobic filler, and anti-flash rust agent in sequence, stir and disperse, and grind to obtain a slurry with a fineness of no more than 40 microns;

[0031] Under stirring, add acrylic emulsion to the slurry, stir and disperse, add cosolvent and remaining defoamer, stir and disperse, add a mixture of thickener and remaining deionized water, mix well to obtain.

[0032] Preferably, the hydroxy-terminated polybutadiene is added to the slurry together with the acrylic ester emulsion.

[0033] In summary, this application has the following beneficial effects:

[0034] This application incorporates a hydrophobic filler with amino and fluorine-containing groups on its surface. The amino groups ensure compatibility with the acrylic emulsion and strengthen the connection between the filler and the coating substrate through chemical bonding, ensuring the coating's strength and wear resistance. The fluorine-containing groups not only improve the coating's salt spray resistance, but also further enhance its hardness and improve its wear resistance. Furthermore, the addition of hydroxy-terminated polybutadiene compensates for any loss in toughness, contributing to overall improvements in the coating's toughness, rigidity, and adhesion, ensuring excellent wear resistance and durability. DETAILED DESCRIPTION

[0035] Preparation Example

[0036] Preparation Example 1: A hydrophobic filler, the preparation steps are as follows:

[0037] Weigh 100g of mica (average particle size of 40 microns) and add it to 1000g of deionized water, dispersing it evenly to prepare a dispersion. The temperature was raised to 80°C, and the pH of the dispersion was adjusted to 9 with 20wt% sodium hydroxide. A precursor solution with a 20% SiO2 mass fraction was prepared using methyl orthosilicate and anhydrous ethanol. 50g of the precursor solution was pumped into the dispersion within 2 hours, and a sol-gel reaction was performed for 2.5 hours to obtain a reaction solution. The reaction solution was separated and filtered, and the filler was washed three times with anhydrous ethanol and dried at 60°C to constant weight to obtain the coated filler.

[0038] Take 100g of coated filler and disperse it in ethanol solution, adjust the pH value to 4, add 12.5g of aminopropyltrimethoxysilane, stir and react for 1h, centrifuge and filter out the precipitate, wash the precipitate with deionized water until neutral, and dry it at 50℃ to constant weight to obtain a silanized filler.

[0039] Weigh 3 g of trifluoroacetic anhydride and add it to 300 mL of dimethylformamide solution, then heat it to 80°C, add silanized filler and sodium hydroxide solution, adjust the pH value to 8.5, and react at 80°C for 3 hours. Filter the precipitate, wash it with deionized water until it is neutral, and dry it at 50°C to constant weight.

[0040] Preparation Example 2: A hydrophobic filler, prepared as follows:

[0041] Weigh 100g of filler (average particle size 40 microns) and add it to 1000g of deionized water, dispersing it evenly to prepare a dispersion. The temperature was raised to 80°C, and the pH of the dispersion was adjusted to 9.5 with 20wt% sodium hydroxide. A precursor solution containing 28% SiO2 by mass was prepared using methyl orthosilicate and anhydrous ethanol. 53.5g of the precursor solution was pumped into the dispersion within 2 hours. A sol-gel reaction was performed for 3 hours to obtain a reaction solution. The reaction solution was separated and filtered, and the filler was washed three times with anhydrous ethanol and dried at 60°C to constant weight to obtain the coated filler.

[0042] Take 100g of coated filler and disperse it in ethanol solution, adjust the pH value to 5, add 14.3g of aminopropyltrimethoxysilane, stir and react for 1h, centrifuge and filter out the precipitate, wash the precipitate with deionized water until neutral, and dry it at 50℃ to constant weight to obtain a silanized filler.

[0043] Weigh 4.2 g of trifluoroacetic anhydride and add it to 500 mL of dimethylformamide solution, then heat it to 80°C, add silanized filler and sodium hydroxide solution, adjust the pH value to 9, and react at 80°C for 3 hours. Filter the precipitate, wash it with deionized water until it is neutral, and dry it at 50°C to constant weight.

[0044] Preparation Example 3, a hydrophobic filler, the preparation steps are as follows:

[0045] Weigh 100g of filler (average particle size 40 microns) and add it to 1000g of deionized water, dispersing it evenly to prepare a dispersion. The temperature was raised to 90°C, and the pH of the dispersion was adjusted to 8.5 with 20wt% sodium hydroxide. A precursor solution with a 20% SiO2 mass fraction was prepared using methyl orthosilicate and anhydrous ethanol. 40g of the precursor solution was pumped into the dispersion within 2 hours. The sol-gel reaction was then carried out for 2.5 hours to obtain a reaction solution. The reaction solution was separated and filtered, and the filler was washed three times with anhydrous ethanol and dried at 60°C to constant weight to obtain the coated filler.

[0046] Take 100g of coated filler and disperse it in ethanol solution, adjust the pH value to 4, add 5.4g of aminopropyltrimethoxysilane, stir and react for 0.5h, centrifuge and filter out the precipitate, wash the precipitate with deionized water until neutral, and dry it at 50℃ to constant weight to obtain a silanized filler.

[0047] Weigh 1.3 g of trifluoroacetic anhydride and add it to 300 mL of dimethylformamide solution, then heat it to 80°C, add silanized filler and sodium hydroxide solution, adjust the pH value to 9, and react at 70°C for 3 hours. Filter the precipitate, wash it with deionized water until it is neutral, and dry it at 50°C to constant weight.

[0048] Preparation Example 4, a hydrophobic filler, differs from Preparation Example 1 in that trifluoroacetic anhydride is replaced by an equal amount of oxalic anhydride.

[0049] Preparation Example 5, a hydrophobic filler, the preparation steps are as follows:

[0050] Weigh 100g of filler (average particle size 40 microns) and add it to 1000g of deionized water, dispersing it evenly to prepare a dispersion. The temperature was raised to 90°C, and the pH of the dispersion was adjusted to 8.5 with 20wt% sodium hydroxide. A precursor solution with a 20% SiO2 mass fraction was prepared using methyl orthosilicate and anhydrous ethanol. 40g of the precursor solution was pumped into the dispersion within 2 hours. The sol-gel reaction was then carried out for 2.5 hours to obtain a reaction solution. The reaction solution was separated and filtered, and the filler was washed three times with anhydrous ethanol and dried at 60°C to constant weight to obtain the coated filler.

[0051] 100 g of the coated filler was dispersed in an ethanol solution, the pH value was adjusted to 4, 5.4 g of aminopropyltrimethoxysilane was added, and the mixture was stirred and reacted for 0.5 h; then 12 g of octadecyltrimethoxysilane was added, and the mixture was stirred and reacted for 1 h; the precipitate was centrifugally filtered out, washed with deionized water until neutral, and dried at 50°C to constant weight to obtain a hydrophobic filler. Example

[0052] Example 1, a salt spray and wear resistant water-based paint for off-road forklifts, the raw material ratio is as follows:

[0053] 10kg acrylic emulsion, 0.06kg wetting agent, 0.2kg dispersant, 0.03kg defoamer, 3.3kg hydrophobic filler, 0.08kg flash rust inhibitor, 0.2kg thickener, 0.35kg cosolvent, 1kg pigment, 0.26kg hydroxyl-terminated polybutadiene, and 6.5kg deionized water. The acrylic emulsion used was WR-886W; the dispersant consisted of a 1:1 fluorocarbon surfactant (YM-3016) and sodium dodecylbenzenesulfonate; the defoamer was BYK-024, and the hydrophobic filler was prepared as in Preparation Example 1; the flash rust inhibitor was PFR289; the thickener was hydroxyethyl cellulose; the cosolvent was dipropylene glycol methyl ether; the pigment was organic pigment 254 Red; the hydroxyl-terminated polybutadiene had a hydroxyl value of 0.54-0.64 mmol / g and a viscosity of ≤4.0 Pa·s.

[0054] The preparation method is as follows:

[0055] Add 60-70 wt% deionized water to a stirred kettle. Add a wetting agent, dispersant, and 40-50 wt% defoamer at 500 rpm and stir at 1000 rpm for 20 minutes. Then, add the pigment, hydrophobic filler, and anti-flash rust agent in sequence at 200 rpm and stir at 1000 rpm for 20 minutes. Then, grind to obtain a slurry with a fineness of 30 ± 5 microns.

[0056] At a rotation speed of 200 rpm, add acrylic emulsion and adhesion promoter to the slurry, stir at 500 rpm for 10 minutes, then add cosolvent and remaining defoamer, stir at 500 rpm for 10 minutes, add a mixture of thickener and remaining deionized water, stir at 800 rpm for 20 minutes, and filter to obtain the product.

[0057] Example 2, a salt spray and wear-resistant water-based paint for off-road forklifts, differs from Example 1 in that the raw material ratios are different, as follows:

[0058] 10kg acrylic emulsion, 0.1kg wetting agent, 0.1kg dispersant, 0.08kg defoamer, 2kg hydrophobic filler, 0.1kg flash rust inhibitor, 0.1kg thickener, 0.2kg cosolvent, 1.2kg pigment, 0.36kg hydroxyl-terminated polybutadiene, and 5.8kg deionized water. The acrylic emulsion used was WR-886W; the dispersant consisted of a fluorocarbon surfactant (YM-3016) and sodium dodecylbenzene sulfonate in a 1:2 ratio by weight; the defoamer was BYK-024, and the hydrophobic filler was prepared according to Preparation Example 2; the flash rust inhibitor was PFR289; the thickener was hydroxyethyl cellulose; the cosolvent was dipropylene glycol methyl ether; the pigment was organic pigment 254 Red; the hydroxyl-terminated polybutadiene had a hydroxyl value of 0.54-0.64 mmol / g and a viscosity of ≤4.0 Pa·s.

[0059] Example 3, a salt spray and wear resistant water-based paint for off-road forklifts, differs from Example 1 in that the raw material ratios are different, as follows:

[0060] 10kg acrylic emulsion, 0.05kg wetting agent, 0.2kg dispersant, 0.1kg defoamer, 4kg hydrophobic filler, 0.1kg flash rust inhibitor, 0.3kg thickener, 0.4kg cosolvent, 1.0kg pigment, 0.5kg hydroxyl-terminated polybutadiene, and 7.3kg deionized water. The acrylic emulsion is WR-886W; the dispersant is a fluorocarbon surfactant (YM-3016) and sodium dodecylbenzene sulfonate in a 1:2 ratio by weight; the defoamer is BYK-024, and the hydrophobic filler is prepared according to Preparation Example 3; the flash rust inhibitor is PFR289; the thickener is hydroxyethyl cellulose; the cosolvent is propylene glycol methyl ether; the pigment is organic pigment 254 Red; the hydroxyl-terminated polybutadiene has a hydroxyl value of 0.54-0.64 mmol / g and a viscosity of ≤4.0 Pa·s.

[0061] Example 4, a salt spray and wear resistant water-based paint for off-road forklifts, differs from Example 1 in that:

[0062] The fluorocarbon surfactant was replaced by an equal amount of sodium dodecylbenzenesulfonate in the dispersant.

[0063] Example 5, a salt spray and wear resistant water-based paint for off-road forklifts, differs from Example 1 in that:

[0064] The sodium dodecylbenzenesulfonate was replaced by an equal amount of fluorocarbon surfactant in the dispersant.

[0065] Example 6 is a salt-spray-resistant and wear-resistant water-based paint for off-road forklifts. The difference from Example 1 is that no hydroxyl-terminated polybutadiene is added. Comparative Example

[0066] Comparative Example 1 is a salt-spray-resistant and wear-resistant water-based paint for off-road forklifts. The difference from Example 1 is that the hydrophobic filler obtained in Preparation Example 1 is replaced by an equal amount of the hydrophobic filler obtained in Preparation Example 4.

[0067] Comparative Example 2, a salt-spray-resistant and wear-resistant water-based paint for off-road forklifts, differs from Example 1 in that the hydrophobic filler obtained in Preparation Example 1 is replaced by an equal amount of the hydrophobic filler obtained in Preparation Example 5.

[0068] Comparative Example 3: commercially available water-based acrylic varnish.

[0069] Performance testing

[0070] 1. Water resistance test: Determine in accordance with the provisions of Method A of GB / T 1733-1993.

[0071] 2. Salt spray resistance test: The test shall be carried out in accordance with the provisions of GB / T 1771-2007. The test shall end when corrosion occurs on the test panel. The test panel shall be observed every 24 hours during the test.

[0072] 3. Wear resistance test: The test was carried out in accordance with the provisions of GB / T 1768-2006 "Paints and varnishes - Determination of abrasion resistance - Rotating rubber grinding wheel method". A CS-10 rubber grinding wheel was selected, the counterweight was 1 kg, the specified number of revolutions was 2000, 5 specimens were taken for each group, and the average mass loss of the specimens was calculated. The test results were accurate to 0.1 mg.

[0073] Table 1. Test results

[0074]

[0075] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A salt spray and wear resistant water-based paint for off-road forklifts, characterized in that: The invention comprises the following raw materials in parts by weight: 90-110 parts of acrylic emulsion, 0.3-1 parts of wetting agent, 1-2 parts of dispersant, 0.1-1 parts of defoamer, 20-40 parts of hydrophobic filler, 0.3-1.2 parts of anti-flash rust agent, 1-3 parts of thickener, 1.5-5 parts of cosolvent, 5-15 parts of pigment, 2-5 parts of terminal hydroxyl polybutadiene, 40-80 parts of deionized water; the preparation method of the hydrophobic filler is: The filler is evenly dispersed in deionized water to obtain a dispersion, the temperature is raised to 80-90° C., and the pH value of the dispersion is adjusted to 8.5-10 with an alkali solution; an ethanol solution of orthosilicate is added as a precursor to the dispersion to perform a sol-gel reaction to obtain a reaction product; Filter, wash the precipitate with water until it is neutral, and dry to obtain the coated filler; Add the coated filler to the ethanol solution, adjust the pH value to 4-5, add the aminosilane coupling agent, stir and react for 0.5-1h, filter, wash with water, and dry to obtain the silanized filler; Prepare trifluoroacetic anhydride solution and heat it to 60-90°C, add silanized filler and sodium hydroxide solution, adjust the pH value to 8-9, react at constant temperature for 2-4 hours, filter, wash with water and dry to obtain.

2. The water-based paint according to claim 1, characterized in that: The filler is selected from at least one of mica, kaolin, calcium carbonate, talc and silica powder.

3. The water-based paint according to claim 1, characterized in that: The solvent of the trifluoroacetic anhydride solution is dimethyl sulfoxide or dimethylformamide.

4. The water-based paint according to claim 1, characterized in that: The mass ratio of the coated filler to the aminosilane coupling agent is 100:5-15.

5. The water-based paint according to claim 1, characterized in that: The molar ratio of the aminosilane coupling agent to trifluoroacetic anhydride is 1:0.15-0.

25.

6. The water-based paint according to claim 1, characterized in that: The dispersant is a fluorocarbon surfactant and sodium dodecylbenzene sulfonate in a mass ratio of 1:1-2.

7. A method for preparing salt spray and wear resistant water-based paint for off-road forklifts, characterized in that: include: According to the raw material ratio of the water-based paint according to any one of claims 1 to 6, weigh the raw materials in the formula for use; Add 60-70wt% deionized water to the preparation container, add a wetting agent, a dispersant, and 40-50wt% defoamer under stirring, stir evenly, add pigment, hydrophobic filler and anti-flash rust agent in sequence, stir and disperse, and grind to obtain a slurry with a fineness of no more than 40 microns; Under stirring, add acrylic emulsion and terminal hydroxyl polybutadiene to the slurry, stir and disperse, add cosolvent and remaining defoamer, stir and disperse, add a mixture of thickener and remaining deionized water, mix well to obtain.

Citation Information

Patent Citations

  • Aqueous high-performance monocomponent primer-topcoat anti-corrosion coating

    CN102796427A

  • Preparation process of super-hydrophobic waterproof coating film

    CN116463040A